2013
DOI: 10.4049/jimmunol.1201015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genetic Variation inNFKBIAand Susceptibility to Childhood Asthma, Bronchiolitis, and Bronchopulmonary Dysplasia

Abstract: Respiratory diseases are the most frequent chronic illnesses in babies and children. Although a vigorous innate immune system is critical for maintaining lung health, a balanced response is essential to minimize damaging inflammation. We investigated the functional and clinical impact of human genetic variants in the promoter of NFKBIA, which encodes IκBα, the major negative regulator of NF-κB. In this study, we quantified the functional impact of NFKBIA promoter polymorphisms (rs3138053, rs2233406, and rs2233… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 63 publications
4
47
0
Order By: Relevance
“…A small number of genes were found to be differentially expressed in cord blood from infants who went on to be hospitalized with RSV versus those that experienced a mild infection, including TNFRSF25 , which is involved in activation of NF-κB (29). Consistent with this, NFKBIA promoter variants which increase toll-like receptor (TLR)-mediated inflammatory cytokine production are associated with severe RSV bronchiolitis and AHR in children with RSV in the first year of life (30). Together this suggests that the immune response to RSV is key to determining the outcome of infection in the very young (Figure 2).…”
Section: Clinical Disease and Treatmentmentioning
confidence: 73%
See 1 more Smart Citation
“…A small number of genes were found to be differentially expressed in cord blood from infants who went on to be hospitalized with RSV versus those that experienced a mild infection, including TNFRSF25 , which is involved in activation of NF-κB (29). Consistent with this, NFKBIA promoter variants which increase toll-like receptor (TLR)-mediated inflammatory cytokine production are associated with severe RSV bronchiolitis and AHR in children with RSV in the first year of life (30). Together this suggests that the immune response to RSV is key to determining the outcome of infection in the very young (Figure 2).…”
Section: Clinical Disease and Treatmentmentioning
confidence: 73%
“…A recent twin study in Denmark concluded that severe RSV bronchiolitis was a marker for genetic predisposition to asthma (184). Furthermore, a genetic polymorphism in the gene encoding IκBα, a negative regulator of NF-κB, was recently identified to be associated with both RSV and asthma (30). In addition, Gern et al showed that infants whose cord blood responded with a stronger IFN-γ secretion to RSV stimulation had reduced risk of early PBW, although the infants in this study were all already at increased risk of wheeze with an atopic background (185).…”
Section: Delayed Sequelae Of Rsv Bronchiolitismentioning
confidence: 99%
“…In line with this, a genetic variant of the best known NF-kB inhibitor, IkBa (NFΚBIA), has been shown to contain inactivating mutations in Hodgkin's lymphoma cell lines and in ∼20% of patients, which leads to strong constitutive NF-kB activity that is thought to contribute to malignant transformation (26,27). Other IkBa variants resulting in decreased expression of the inhibitor have been described in inflammation-associated disorders including asthma and bronchiolitis (28). The existence of regulatory proteins that lead to inactivation of NF-kB provides a rationale to consider that a genetic variant that reduces their inhibitory activity may be clinically relevant in chronic inflammatory disorders where NFkB is constitutively active.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping was performed by real time PCR assays using allele-specific Taqman probes (Fig. 1) as previously described [27], [28].…”
Section: Methodsmentioning
confidence: 99%